Should the Equality Act 2010 Be Extended to Prohibit Appearance Discrimination?. (May 2022) - Mason, Andrew; Minerva, Francesca
The UK Equality Act 2010 prohibits direct and indirect discrimination with respect to nine characteristics: age, disability, gender reassignment, marriage and civil partnership, pregnancy and maternity, race, religion or belief, sex, and sexual orientation. We argue that the best way of understanding the Act is to see it as protecting those who are vulnerable to systematic disadvantage, partly in virtue of being at risk of experiencing discrimination that violates what we call the meritocratic principle. If this is a key principle underpinning the Act, then there is a compelling case for extending the legislation to include the protection of at least one further characteristic, namely, appearance . We consider but reject various difficulties that might be raised with extending the Act in this way, including the objection that those vulnerable to forms of appearance discrimination that violate the meritocratic principle could be adequately protected by treating them as disabled.